Perceptions of the Titicaca Grebe (Rollandia microptera) in a Peruvian Aymara Fishing Village - Quispe, Jhazel; Villar, Daniel; Zapana, Joel; Thomsen, Bastian; Gosler, Andrew G. (Ethnobiology Letters, 2023)
This paper presents a qualitative analysis of people’s attitudes and knowledge of the endangered endemic Titicaca Grebe (Rollandia microptera) in the Aymara fishing village of Karana, Peru, on the shores of Lake Titicaca. Most respondents hold no strong opinions on the Titicaca Grebe, and those who do tend to be hostile towards it. Hostility towards the species tends to come from fishers, who view the species as competition for fish and blame it for breaking their nets. As the majority of the interviewees lack formal environmental education, we suggest that increased environmental education about the grebe’s endemic and endangered status may move some people from apathy towards support for grebe conservation. Since most of the source of the hostility towards the grebe from fishers stems from perceived competition with it for fish and its role in breaking nets, we suggest that further study of grebe diet and bycatch is needed to reduce direct grebe-fisher conflict. We also discuss the potential future of grebe-fisher conflict, as many of the fishers of Lake Titicaca begin to transition to pisciculture. This study is a pilot study for future conservation work on local attitudes and local ecological knowledge across the entirety of Lake Titicaca. It therefore informs as to how to conduct ethnobiological research in the region. We discuss what we learned about conducting ethnobiological research in the high Andes and how this study informed that larger ethnobiological project.